Stress, Coping, and Quality of Life in Families with a Child with ASD Living Regionally - Parsons, Dave; Cordier, Reinie; Lee, Hoe; Falkmer, Torbjorn; Vaz, Sharmila (2020)
Objectives: The present study aimed to explore whether regionality is associated with differing stress levels, coping, QOL and daily routines for parents and families of a child with ASD (aged 2–18 years) in Western Australia using validated outcome measures and compare the stress levels and QOL of this group to population norms. Methods: A sample of 278 families living in Western Australia who have a child or adolescent (2–18 years old) with a clinical diagnosis of ASD participated in a cross-sectional survey. Multivariate logistic regression modelling was conducted to determine key factors associated between regionality and demographic variables, quality of life, coping styles, time use, and stress levels. Results: Parents living in low densely populated areas were more likely to adopt avoidant coping mechanisms, compared to those living in densely populated areas. Fathers with children on the autism spectrum were less likely to be educated above diploma level in regional and remote areas. Stress, QOL or daily routines did not differ by regionality; however, the total sample (i.e., parents from both LDP and DP areas) experienced significantly higher levels of stress and lower QOL when compared to the general population. Conclusions: The findings suggest that despite having higher levels of stress and lower QOL compared to the general population, residing in a geographically LDP area in Western Australia has a small association on preferred coping style preference and has no association on stress levels, QOL or daily routines for parents who have a child with ASD.